Developing Constructivist-Webquests Online Materials for TEFL Course - Wahyu Kyestiati Sumarno; Tatik Tatik; Ali Shodikin (Metathesis: Journal of English Language, Literature, and Teaching, 2017)
Considering the results of researchers’ observation at some Teaching English as A Foreign Language (TEFL) classes, which noted that there were at least two problems, namely the lack of materials to accommodate the students’ need of learning and unavailability of TEFL media to support the learning process, the development of materials for TEFL class are urgently needed. Besides, the high demand for technology integration into language learning to face digital environment motivates education practitioners to develop materials with technology application. WebQuests can be one of meeting points for this intersection. A WebQuests is an online media which allows students to collect and construct information about a subject using a web. By using WebQuests, the students will have an opportunity to actively contribute constructing their own knowledge during the teaching and learning process. Therefore, this study aims at giving rational and theoretical background in developing a web-based material with a constructivist approach, named constructivist-WebQuests.Keywords:material development, constructivist-WebQuests, online materials, TEFL